2018
DOI: 10.1002/bmc.4326
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of eight components in Angelica sinensis based on UHPLC‐ESI‐MS/MS method for quality evaluation

Abstract: A method employing ultra-high performance liquid chromatography-tandem mass spectrometry (UHPLC-MS/MS) for determination of eight components including ferulic acid, senkyunolide A, butylphthalide, ligustilide, butylidenephalide, senkyunolide I, senkyunolide H and levistolide A in Angelica sinensis was established. The separation was carried out using a Waters ACQUITY UHPLC BEH C column with gradient elution with 0.1% formic acid aqueous and acetonitrile at a flow rate of 0.4 mL/min. Good linearity was attained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 12 publications
3
7
0
Order By: Relevance
“…However, we examined β-eudesmol at 100 μmol/L and found out no activity, as shown in Supplementary Figure S1. Levistolide A, the other NGF-increasing active ingredient identified in this study, is found in CR (Zuo et al 2011) and JAR (Gui and Zheng 2019). However, CR was unable to increase NGF in our study, as the concentration in the CR extract might have been low.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…However, we examined β-eudesmol at 100 μmol/L and found out no activity, as shown in Supplementary Figure S1. Levistolide A, the other NGF-increasing active ingredient identified in this study, is found in CR (Zuo et al 2011) and JAR (Gui and Zheng 2019). However, CR was unable to increase NGF in our study, as the concentration in the CR extract might have been low.…”
Section: Discussionmentioning
confidence: 60%
“…In addition, to identify NGF enhancers in TSS, 30 compounds present in TSS were examined at a single concentration (100 μmol/L); the results are shown in Supplementary Figure S1. Atractylodin, which is present in ALR (Chen et al 2012), and levistolide A, which is present in CR (Zuo et al 2011) and JAR (Gui and Zheng 2019), significantly enhanced NGF production in astrocytes. These active ingredients further showed concentration-dependent actions (Figure 8).…”
Section: Resultsmentioning
confidence: 99%
“…Melampyroside is an iridoid compound, and its relative peak areas in the ethyl acetate and n-butanol extracts reached 11.39% and 13.31%, respectively. Iridoids have been studied for their anti-inflammatory activity (Gui and Zheng, 2018). Taken together, the four selected compounds were representative and formed a basis for the verification experiment.…”
Section: Compound Analysismentioning
confidence: 99%
“…levistolide A (Gui and Zheng, 2019). The volatile oil of A. sinensis, has evident antiinflammatory activities (Zhong et al, 2016).…”
Section: Salvia Miltiorrhiza Bunge[lamiaceae] (Dangshen)mentioning
confidence: 99%